2022
DOI: 10.1186/s40623-022-01690-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of projectile shape and interior structure on crater size in strength regime

Abstract: Experiments on crater formation in the strength regime were conducted using projectiles of various shapes with an aspect ratio of ~ 1, including both solid and hollow interiors. The surface diameter, inner (pit) diameter, and depth of the craters on basalt and porous gypsum targets were measured. Using the bulk density of the projectile, the surface diameter and depth for basalt and the pit diameter and depth for porous gypsum were scaled using the pi-scaling law for crater formation in the strength regime. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…In laboratory impact-cratering experiments in the field of planetary science, the projectiles used have generally been solid because the original purpose was to simulate the impacts of celestial bodies. In contrast, the number of crater-formation experiments using hollow or internally structured projectiles is limited (e.g., Schultz & Gault 1985;Schultz et al 2010;Hermalyn et al 2012;Kadono et al 2022). Despite such a situation, it has been found that crater size can be determined by considering the outer diameter and bulk density of such projectiles, as in the case of solid projectiles (e.g., Schultz & Gault 1985 in a gravity regime and Kadono et al 2022 in a strength regime).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In laboratory impact-cratering experiments in the field of planetary science, the projectiles used have generally been solid because the original purpose was to simulate the impacts of celestial bodies. In contrast, the number of crater-formation experiments using hollow or internally structured projectiles is limited (e.g., Schultz & Gault 1985;Schultz et al 2010;Hermalyn et al 2012;Kadono et al 2022). Despite such a situation, it has been found that crater size can be determined by considering the outer diameter and bulk density of such projectiles, as in the case of solid projectiles (e.g., Schultz & Gault 1985 in a gravity regime and Kadono et al 2022 in a strength regime).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the number of crater-formation experiments using hollow or internally structured projectiles is limited (e.g., Schultz & Gault 1985;Schultz et al 2010;Hermalyn et al 2012;Kadono et al 2022). Despite such a situation, it has been found that crater size can be determined by considering the outer diameter and bulk density of such projectiles, as in the case of solid projectiles (e.g., Schultz & Gault 1985 in a gravity regime and Kadono et al 2022 in a strength regime). This implies that the crater size does not depend on the details of the projectile structure because the structure of the projectile is destructed by the high pressure caused by impact velocities exceeding several hundred meters per second.…”
Section: Introductionmentioning
confidence: 99%